Upaya meningkatkan hasil belajar lompat jauh dengan menggunakan metode permainan engklek - Prasetio, Aditia Dwi; Basri, Hasan (Motion: Journal Research of Physical Education, 2022)
This study aims to find out how to improve long jump learning outcomes by using the crank game method for class VIII students at SMP Negeri 36 Kota Bekasi. The problem in this research is the teacher's efforts to improve the long jump learning outcomes by using the Engklek game method which is easy and fun for students who study it. The method used in this research is the classroom action research method, namely by providing long jump learning using the Engklek game method. . Before and after being taught pre- and post-tests were carried out to see how far the long jump learning outcomes had increased using the crank game method. The research subjects were taken by 18 class VIII students of SMP Negeri 36 Bekasi City. In this research, the results of the initial, final and improvement tests of the subjects were processed and statistically analyzed, with the following calculation results: , and in cycle II the results showed that 88.89% of students passed the KKM or 16 students out of 18 students.